Analisis Strategi Pemasaran Digital Pada Toko Baju Busana Cahaya Indah di Daerah Telang Dalam Perspektif Ekonomi Syariah - Muklis, Moh; Rosadi, Muhammad Iqbal; Rohman, Abdur (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the digital marketing strategies implemented by clothing stores in the Telang area from a sharia economic perspective. In the digital era, business actors are required to adapt to technology, including in terms of promotion and marketing. The approach used in this study is descriptive qualitative, with data collection through observation, interviews, and documentation. The results of the study show that most business actors have utilized social media such as WhatsApp, Instagram, and Facebook Marketplace to market their products. The strategies implemented are mostly in line with the principles of sharia economics such as honesty (ṣidq), openness (tabligh), and amanah. However, some practices that are not in accordance with sharia are still found, such as the use of photos that do not match the original product (gharar) and excessive promotion (tadlis). The main inhibiting factors in the implementation of sharia digital strategies are limited digital literacy and infrastructure. Therefore, ongoing assistance and training in sharia-based digital marketing are needed to improve understanding and business practices in accordance with Islamic values.